(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Teachers with a quality ’reliable’ for teaching are the individuals who are committed, enthusiastic and intellectually and emotionally energetic in their work with children. These teachers know about the difficulties of the more extensive social settings in which they instruct, have an unmistakable feeling of personality and trust that they can have any kind of effect to the learning and achievement of every one of their understudies. They care profoundly about them. They care likewise about how and what they educate and are curious to get familiar with both so as to wind up and stay more than just competent. They know about the role played by emotions in classroom teaching. They are committed to work in co-activity and collaboration with associates. For these teachers, teaching is a creative and adventurous profession.